The Influence of Institutional Ownership and Capital Intensity Moderated by Company Size on Tax Avoidance - Aprilia, Delina; Melzatia, Shinta (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
This research aims to analyze and obtain empirical evidence regarding the influence of institutional ownership and capital intensity moderated by company size on tax avoidance. The independent variables used in this study are institutional ownership and capital intensity. The dependent variable used in this study is tax avoidance. The moderating variable in this study is the size of the company. The data used in this study are secondary data obtained from the official website of the Indonesia Stock Exchange and the official websites of each company. The population in this study consists of 68 property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2023. With the purposive sampling technique, a sample of 17 property and real estate companies listed on the Indonesia Stock Exchange was obtained. The data analysis method in this study uses multiple linear regression analysis and moderation regression analysis.